2021
DOI: 10.3390/cancers13164170
|View full text |Cite
|
Sign up to set email alerts
|

Plasmalogen Deficiency and Overactive Fatty Acid Elongation Biomarkers in Serum of Breast Cancer Patients Pre- and Post-Surgery—New Insights on Diagnosis, Risk Assessment, and Disease Mechanisms

Abstract: The polyunsaturated fatty acid (PUFA) elongase, ELOVL5, is upregulated in breast cancer (BC) vs. adjacent normal tissue. We performed a comprehensive lipid metabolomic analysis of serum using high-resolution accurate mass spectrometry from two case-control studies that included non-BC, BC subjects pre-surgery, and BC subjects one-month post-surgery to determine if the metabolic signatures of over-active fatty acid elongation and other lipid changes could be detected in BC vs. non-BC subjects: study 1 (n = 48: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 43 publications
1
6
0
Order By: Relevance
“…Therefore, we hypothesize that PLs’ increases are needed to sustain tumor growth, both by enhancing membrane biosynthesis, including for endoplasmic reticulum capacity enhancement and particularly to support extended protein glycosylation . Hence, increased PL levels (namely, PtdCho, SMs, PtdEtn, and Pls, in decreasing order of abundance) are confirmed as differentiators of tumoral tissue from healthy tissue and of tumors of increasing aggressiveness, as reported in previous studies of BC. , However, to our knowledge, these changes were here observed for the first time as accompanying the HD to HI, and to HIR, transitions in the MPA mouse model of BC. Indeed, in HIR tumors, these increases are consistent with the lowest GPC levels previously reported for the same tumors (Figure ).…”
Section: Discussionsupporting
confidence: 81%
“…Therefore, we hypothesize that PLs’ increases are needed to sustain tumor growth, both by enhancing membrane biosynthesis, including for endoplasmic reticulum capacity enhancement and particularly to support extended protein glycosylation . Hence, increased PL levels (namely, PtdCho, SMs, PtdEtn, and Pls, in decreasing order of abundance) are confirmed as differentiators of tumoral tissue from healthy tissue and of tumors of increasing aggressiveness, as reported in previous studies of BC. , However, to our knowledge, these changes were here observed for the first time as accompanying the HD to HI, and to HIR, transitions in the MPA mouse model of BC. Indeed, in HIR tumors, these increases are consistent with the lowest GPC levels previously reported for the same tumors (Figure ).…”
Section: Discussionsupporting
confidence: 81%
“…There are diverse models for breast cancer, based on metabolic heterogeneity, stromal immune phenotype, diverse cell-death patterns, cell necroptosis, plasmalogen deficiency, overactive fatty acid elongation biomarkers, and 4-mRNA metastasis-related genes ( Xie et al, 2018 ; Zheng et al, 2020 ; Tomida et al, 2021 ; Yu et al, 2021 ; Xie et al, 2022 ; Zou et al, 2022 ). Yu et al demonstrated that energy-related metabolic features in BC were related to glycolytic activity and survival.…”
Section: Discussionmentioning
confidence: 99%
“…Plasmalogen levels are reduced in SLE patients and are correlated with increased oxidative stress ( 66 ). Nguma et al, have suggested that ethanolamine plasmalogens may even serve a protective role against oxidative stress and have studied the utility of these molecules in the treatment of colitis in murine models ( 67 ). Levels of several choline plasmalogens were found by Nishimukai et al to have a strong inverse correlation to progression of atherosclerosis and have even been suggested as possible biomarkers of CVD ( 68 ).…”
Section: Discussionmentioning
confidence: 99%